(untitled) (IPS Journal of Public Health, 2023)
The quality of care a woman experience during the prenatal, intrapartum and postpartum period has a direct impact on her health and the health of her child, and it might also affect her decision to seek care in the future. This study evaluated the quality of maternal health services in selected primary health centers in Rivers State. The study design was cross-sectional study design. Multistage sampling was used to select seven Primary health centers (PHCs) while simple random sampling was used to select 384 post-natal mothers across the selected PHCs. Self-administered questionnaire and checklist were used to assess the postnatal mothers and primary health centers respectively. The questionnaire collected data on socio-demographic variables, levels of satisfaction and factors influencing the quality of maternal health services while the checklist collected data on the extent to which the facilities have the capacity to support quality maternal health services. Three hundred and forty-one questionnaires and the entire checklist used for the survey were retrieved. SPSS V22 was used in the analytical process and data was analyzed using descriptive statistics. Results revealed that 40.2% of the postnatal mothers were within age 26-33 years, 54.8% had secondary school as their highest educational level and 85% were married. Majority of the mothers were satisfied with the maternal healthcare services in PHCs in Rivers State, mean was 102.24±11.68; the perceived factors influencing the quality of maternal health services in PHCs in Rivers State include, healthcare delivery (96.2%), adequate human and material resources (94.1%), staff conduct and practice (86.2%) and physical facilities (84.5%); although PHCs with facilities that are available and in good condition were 85.7% they are not fully equipped to support quality basic obstetric emergency care.